Human capital development and SME growth: The mediating role of business productivity - AB, Nizhamuddin; Juliana, Ahmad (Journal of Management and Digital Business, 2025)
Sustainable growth in small and medium-sized enterprises (SMEs) is not determined solely by access to capital and markets, but also by the quality of the human resources managing the business. This study aims to analyse the role of human resource development in promoting SME growth through business productivity. Human resource development is represented by HR training and the SME operator competence. This study employed an explanatory quantitative approach involving 180 SME operators in North Kalimantan. Data were collected through a Likert-scale questionnaire and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings show that HR training and the SME operator competence have a positive and significant relationship with business productivity and SME growth. Business productivity is also positively associated with SME growth and mediates the relationship between HR training, SME operator competence, and SME growth. These findings emphasise that SME strengthening strategies should be directed towards improving practical skills, entrepreneurial competence, operational efficiency, innovation, and productivity so that business growth can become more adaptive and sustainable, particularly in developing regions that require local resource-based economic competitiveness.